A uniform disc is rotating with angular velocity ω and then it is gently placed horizontally on a rough horizontal surface having a coefficient of friction μ . The total time T taken by disc to stop rotating completely can be expressed as
T = b a × μ g ω R .
Find The value of a × b .
Details:
∙ 'a' and 'b' are Co-prime positive integers.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution Deepanshu. :)
I founded angular acceleration by a slightly different method.
I found torque acting on ring with inner and outer radius r and r + d r respectively.
Mass of this ring d m = π R 2 2 π r d r m
Now ∫ d τ = ∫ μ d m g r
So torque is 3 2 μ m g R
So angular acceleration is 3 2 μ m g R ÷ 2 1 m R 2 = 3 R 4 μ g
I solved this in second attempt because I thought that I have to find the value of a + b . :(
Log in to reply
Great ! That's nice Approach! :) Initially I also thought this same method but then i feel doubt that is friction on whole ring is constant or variable ... So I left that and starts from more basics And but later I found that it is constant on a ring !! And yes generally we have to calculate 'a + b' Mostly in all question of brilliant so it is our habit So I understand your situation :)
So if we consider the expression of torque due to friction,can we conclude that the point of application of frictional force is at a distance of 2R/3 from the centre of disk?
I solved this question recently in IE Irodov.
What if the disk was rotating about its periphery.
Log in to reply
Well that is also simple . It just use one level above calculus . But yet simple ! I think great jatin yadav already posted that question. You should serch that .
In eq-->(2) you've mistyped R^4 as R^2. Anyways great solution. 👍 Kudos to you
Problem Loading...
Note Loading...
Set Loading...
d m = σ x d θ ( d x ) d f = μ ( d m ) g = σ μ g ( x d x ) d θ .
Now torque due to this is:
d τ = ( d f ) x d τ = σ μ g ( x 2 d x ) d θ ∫ d τ = σ μ g ∫ θ = 0 θ = 2 π d θ ∫ 0 R x 2 d x τ = 3 2 π σ μ g R 3 . . . . . . . . ( 1 ) τ = I α = 2 m R 2 α = 2 σ π R 2 α . . . . . . . ( 2 ) ⇒ α = 3 R 4 μ g 0 = ω − α T ⇒ T = 4 μ g 3 ω R .